Gedhe Kauman Mosque Introduction Application Based On Mobile Augmented Reality - Muhammad Fadhlurrohman; Adam Sekti Aji (Publikasi Indonesia, 2024)
The Great Mosque of Yogyakarta, or better known as the Greatness of the Grand Mosque, is an integral part of the Yogyakarta Sultanate. The existence of this mosque confirms the existence in Yogyakarta as an Islamic kingdom. The gedhe mosque was built on the west side of the north square and southwest of the Beringharjo market, not far from the palace buildings. The Gedhe Mosque was founded on Sunday, May 29, 1773 M. or 6 Rabi'ul Akhir 1187 H. This research aims to design an Augmented Reality-based application that can make it easier for tourists to recognize history and objects in the Gedhe Kauman mosque. The application was built using the Unity 3D application. The Gedhe Kauman Mosque Introduction Application is used as an introduction and learning medium for the Gedhe Kauman mosque for tourists and the surrounding community. The use of this application is recommended to use android with version 8.1 (Oreo) and above.